Prunus amygdalus extract exert antidiabetic effect via inhibition of DPP-IV: in-silico and in-vivo approaches. Issue 11 (24th July 2021) - Kumar, Vikas; Sachan, Richa; Rahman, Mahfoozur; Sharma, Kalicharan; Al-Abbasi, Fahad A.; Anwar, Firoz
Abstract: Prunus amygdalus ( PA ) is a popular invasive seed utilized in the management of diabetes in Jammu and Kashmir, India. The objective of the current study was to scrutinize the antidiabetic effect of Prunus amygdalus (PA) against Streptozotocin (STZ) induced diabetic rats and explore the possible mechanism of action at cellular and sub-cellular levels. Box Benkan Design (BBD) was performed to determine the effect of PA powder to methanol, extraction time and extraction temperature on DPPH and ABTS free radical scavenging activity of decoction. In-silico study was performed on GLUT1 (5EQG) and dipeptidyl peptidase IV (DPPIV) (2G63) protein. Type II diabetes mellitus was initiated by single intra-peritoneal injection of STZ. The Blood Glucose Level (BGL) and body weight were estimated at regular interval of time. The different biochemical parameters such as hepatic, antioxidant, and lipid parameters were estimated. At end of the study, pancreas was used for histopathological observation. The variation in DPPH antiradical scavenging activity 40.0–90.0% and ABTS antiradical scavenging activity 34–82%, were estimated respectively. STZ induced DM rats showed increased BGL at end of the experimental study. PA treatment significantly ( p  < 0.001) down-regulated the BGL level. PA significantly ( p  < 0.001) altered the biochemical, hepatic and antioxidant parameters in a dose-dependent manner. Histopathological examination demonstrated the constructive mass of β-cells in pancreas. Overall, the current study indicates that the PA treatment down-regulated the hyperglycemic, oxidative stress and hyperlipidaemia in diabetic rats, due to inhibition of enzymes or amelioration of oxidative stress. Communicated by Ramaswamy H. Sarma